Endoscopy on the way to molecular imaging: Endocytoscopy Endoskopie auf dem weg zur molekularen bildgebung: Endozytoskopie - Neumann, Helmut; Langner, C.; Vieth, M.; Neurath, Markus (Verdauungskrankheiten, 2012)
Endocytoscopy is a new imaging modality which enables in vivo microscopic imaging of the mucosa at 1.400-fold magnification. Various studies have addressed the potential of endocytoscopy for different disease entities. including esophageal squamous cell carcinoma. celiac disease and colorectal polyps. In this review we will focus on the technique of endocytoscopy and potential applications. Furthermore, we will give an outlook on future possible applications of this emerging endoscopic imaging technique.© 2012.
CRIS-Team Scopus Importer:2025-03-05
Keywords: Chromoendoscopy; Endocytoscopy; Endomicroscopy; Endoscopy; In vivo histology; Molecular imaging; Optical biopsy